Student’s Accreditation of integrated Medical Education in Nepal - Banerjee, Indrajit; Jauhari, Akhilesh Chandra; Johorey, Ajay Chandra; Gyawali, Sudesh; Saha, Archana (Asian Journal of Medical Sciences, 2011)
Objective: Course curriculum of medical sciences is made by learned professors of Universities, politicians and the government officers in education ministry without consulting the students for whom it is made. Student’s Accreditation of curriculum may be useful in further modification of teaching & learning methods. In Nepal, Medical education is an experimental integrated teaching of four and half years for MBBS degree is going on for more than two decades, until now no Accreditation has been done as to what type of Doctors we are producing. The aim of the study was to find out whether integrated teaching or classical medical studies produce better doctors. Material & Methods: The study was conducted from November 2009 to February 2010 at Manipal college of Medical Sciences, Pokhara, Nepal. The present study was done to asses the teaching/learning and evaluation procedures adopted by getting Accreditation from students of 2nd, 3rd and 4th semester A structured questionnaire was prepared and a pilot study consisting of 10 students from each batch (randomly selected) was done. Results were analyzed and discussed by the authors before undertaking the main study. Later in the main study accreditation of 186 medical students was collected by same multigraded questionnaire and analyzed for the benefit of further modification of medical education by universities and medical colleges in Nepal in particular and general elsewhere. Results: All the results of the study were discussed in detailed one by one in discussion .Out of them for example one of the result of the study was that subjects like Pathology, Microbiology & Pharmacology should be reduced or not at all taught in first 2 semesters and should be continued till 7th semester like community medicine when the students attend clinical subjects for better understanding of medicine and producing better doctors. Conclusion: Overall the results were alarming & may be taken up seriously by the policy makers. They can bring about amendments in course curriculum of universities in future. Key Words: Medical Education; Multigraded Questionnaire; Bachelor of Medicine & Bachelor of Surgery DOI: 10.3126/ajms.v2i1.3592 Asian Journal of Medical Sciences 2 (2011) 49-52